Demand side management of an urban water supply using wholesale electricity price. (1st March 2017) - Kernan, R.; Liu, X.; McLoone, S.; Fox, B.
Highlights: The proposed method provides a realistic method of cost minimisation in a water supply system. Optimisation was carried out on the basis of wholesale electricity cost. This method encourages wind power utilisation without explicit operator intervention. The method was demonstrated on a benchmark simulation system as well as a real water supply network. Water utility costs decreased significantly while wind power utilisation increased. Abstract: Municipal water supply consumes large quantities of electrical energy to move water from catchment areas to service reservoirs near centres of population. Pumping does not necessarily occur round the clock, but rather when necessary to uphold constraints relating to reservoir levels and system pressure. There is a degree of flexibility in the timing of pumping that makes it an excellent candidate for Demand Side Management, meaning that it can provide opportunities for improving power system operation and reducing electricity costs for the water utility. The extent of this flexibility depends on a number of factors. This study examines the optimisation of two water supply systems - the 'Van Zyl' benchmark system and a representation of the supply for the city of Belfast, Northern Ireland. The potential to employ intelligent operation of pumps to help bolster uptake of variable wind generation is assessed, as is quantification of the potential savings for a water utility. The results show significant potential savings for the water utility as well as a substantial increase in the utilisation of wind power.